EFFECT OF MELON PEELING MACHINE PROJECT ON STUDENT ACHIEVEMENT IN TECHNICAL EDUCATION (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Practical projects in technical education play a crucial role in enhancing students’ skills and knowledge. This study investigates the impact of a melon peeling machine project on student achievement in technical education programs. The project aims to provide hands-on experience and improve students’ understanding of mechanical design and fabrication processes. A quasi-experimental design was employed, involving 100 students from two technical education institutions in Rivers State, Nigeria. The students were divided into a control group and an experimental group. The experimental group participated in the melon peeling machine project, while the control group followed the standard curriculum without the project. Data on student achievement were collected using pre- and post-tests, practical assessments, and student feedback surveys. Statistical analysis was conducted using SPSS version 25.0. The results indicated a significant improvement in the achievement scores of students in the experimental group compared to the control group. The mean post-test scores of the experimental group were 85% higher than their pre-test scores, while the control group showed a 45% improvement. Practical assessments revealed that students who participated in the project demonstrated better understanding and application of mechanical design principles. Student feedback highlighted increased motivation, engagement, and confidence in technical skills. The melon peeling machine project had a positive effect on student achievement in technical education. The hands-on experience provided by the project enhanced students’ practical skills, understanding of mechanical design, and overall academic performance. Incorporating similar projects into technical education curricula can significantly improve student outcomes and better prepare them for industry demands.